HUBUNGAN PENGETAHUAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISISTERHADAP KEPATUHAN DIETDI RSI MALAHAYATI - Basri Basri (Jurnal Maternitas Kebidanan, 2019)
Knowledge and compliance are the key to health in patients with chronic renal failure undergoing hemodialysis therapy, a diet that is consumed in excess or less will cause side effects in patients, while patients with chronic renal failure often experience deficits in nutritional intake. The purpose of this study was to determine the relationship between the level of knowledge and level of dietary compliance in patients with chronic renal failure undergoing hemodialysis therapy in an Islamic hospital instead of terrain. The method used was an observational analytic population of all patients with chronic renal failure, all patients with chronic renal failure undergoing hemodialysis therapy at an Islamic hospital actually had a field of 33 patients using a total sample. Data collection used questionnaires, independent variables of knowledge and dependent variables on diet compliance. Data were analyzed with significance α = 0.05. The results of the study showed that most (72.7%) respondents had good knowledge and almost all respondents (93.9%) were obedient in dieting. The results of the analysis obtained are ρ = 0.011, ρ> 0.005 meaning that there is no significant relationship between knowledge and dietary compliance. Knowledge greatly affects adherence to a person's diet, there are other things that affect such as patient experience, social, economic conditions, patient psychological factors, and family support for patients. For patients with chronic kidney failure who undergo hemodialysis therapy should maintain their knowledge and also be able to advise patients who have recently undergone hemodialysis therapy from their past experience and for colleagues to always give enthusiasm and motivation to patients and provide support for knowledge and information.